Research Note: Stream water quality of a Community-Based Forest Management (CBFM)-protected watershed in Baybay, Leyte, Philippines - Pasa, Arturo E. (Annals of Tropical Research, 2008)
The study assessed the quality of stream water of the watershed within the Community-Based Forest Management (CBFM) Project in Cienda, Gabas, Baybay, Leyte, Philippines. Results showed that, on the average, streamflow velocity was 0.30m/sec, streamflow volume 0.32m3/sec, turbidity 2.96 ntu and the associated sediments 16.0mg/ L. Odor and taste were unobjectionable. pH ranged from 7.50 to 7.0 while total hardness from 7.84 to 15.16 mg/L. The average nitrite (NO2) content was 11.115mg/L while nitrate (NO3) was 1.05 mg/L. The concentration of nutrients was also very low. Phosphorus (P) ranged only from 2.20 to 4.46 mg/kg or parts per million (ppm) while potassium (K) ranged from 3.71 to 3.90 ppm. Sodium (Na), calcium (Ca), and magnesium (Mg) concentrations were also very low. Heavy metals were detected but also at low concentrations.